DEVELOPMENT OF AN EDUCATIONAL ONLINE GAME FOR THE INTERVENTION OF KOREAN DYSLEXIA - A GAME UTILIZING SYLLABLE COUNTING FOR PHONOLOGICAL AWARENESS INTERVENTION - - Kim, Songyi; Park, Inchan; Yang, Minwha; Lee, Aejin; Kang, Soyoung (PEOPLE: International Journal of Social Sciences, 2017)
5% of the world population suffers from dyslexia (difficulty in reading), and according to research, the brain begins to distinguish characters at the age of 60 months. Thus, at the time when children are learning to speak at the age of 60 months, the dyslexic intervention is most needed. During intervention, the teacher needs to use a verified method according to the educational needs of the students with dyslexia. In Korea, the number of teachers specialized for dyslexia education is highly insufficient. Therefore, a program that accessible to as many dyslexic children as possible in highly in need which can offered independent yet effective learning. This study aimed to develop an effective online game program for the treatment of dyslexia. We first researched the contents and characteristics of the current phonological dyslexia interventions, and examined the needs of stakeholders. Then, based on the survey results, we designed a game for phonological awareness (syllable counting).